The Impact of Globalization on Islamic Values ​​and the Identity of Islamic Religious Education - Firma Linda Aida; Nur Khasanah (CV Kalimasada Group, 2025)
Purpose - This study examines how globalization affects Islamic religious values and the identity of Islamic education. It aims to identify both the opportunities and challenges brought by globalization in shaping the character and values upheld within Islamic educational institutions. Design/Methodology/Approach - The study employs a qualitative analytical approach by examining the dynamics of globalization technological, economic, cultural, and social and analyzing their implications for the preservation and transformation of Islamic educational values. Findings - The results indicate that globalization provides opportunities for the advancement of science and technology; however, it also poses challenges such as cultural shifts, weakened spirituality, and the rise of materialistic and individualistic lifestyles. The study highlights the importance of reinforcing Islamic core values justice, solidarity, and spirituality—to maintain the identity of Islamic education amid rapid global change. Originality/Value - This study contributes to the discourse on Islamic education by offering a contemporary analysis of how globalization influences religious values and identity. It emphasizes the need for strategic strengthening of Islamic educational identity so that learners can adapt to global developments without abandoning their fundamental religious values.